If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = -1y + 6 Reorder the terms: 3 = 6 + -1y Solving 3 = 6 + -1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add 'y' to each side of the equation. 3 + y = 6 + -1y + y Combine like terms: -1y + y = 0 3 + y = 6 + 0 3 + y = 6 Add '-3' to each side of the equation. 3 + -3 + y = 6 + -3 Combine like terms: 3 + -3 = 0 0 + y = 6 + -3 y = 6 + -3 Combine like terms: 6 + -3 = 3 y = 3 Simplifying y = 3
| t*5-4=14 | | 88m^2=3+w | | -6(-3x+6)=90 | | x-2(2x-5)=8 | | 37.50-0.5x=42.75-0.75x | | 15x^2+20x-20=0 | | -109=3-4(8n+4) | | x+82+x+102=180 | | log[2](5x+6)=5 | | 7(t-3)+8t=5(3t+4)-11 | | d+20+0.2d= | | t(x)=11x-725 | | (2x-3)squared=5 | | 5+2x=234234325.00302030303030303030101010324234 | | 2(8n-1)=126 | | 6d+3d+2d-6=3d | | 7v+12b=694 | | X-4x-7=5x(x+21) | | 2(7-2n)=87 | | a*4+8=11 | | 5+x+x+3=32 | | 12x+26=6x+116 | | 5+0.05x= | | d-1.9=9.1 | | 36=-4v | | 10m-22=68 | | 7+12z-5=9z+42-7z | | (x+2)(3x-2)=28 | | 3a+2b=29+a+b | | 4x^2+5x+1=52 | | 43-3x=1x+9 | | -9+x=x |